PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANSASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN BIDANG CORN STARCH DAN SWEETENER PT MIWON INDONESIA GRESIK - RIFQI D, FAKHRI (Jurnal Ilmu Manajemen (JIM), 2017)
Economic development in the era of globalization is much influenced by the increasingly strict business competition. Many of the challenges to be faced by the company. Companies need to keep the quality of the human resources (HR). PT. Miwon Indonesia Gresik is a company that focuses on the industry Monosodium Glutamate (MSG) or among people known by the term flavoring located at jl. Driyorejo No. 1 Gresik. This company has been established since 1973 through PT Miwon Indonesia. Products by PT Miwon Indonesia such as Miwon, Mamasuka, Miwon Packaging, and Chung Jung Won. At present there are two factories from PT Miwon located in Jalan Driyorejo Gresik which is adjacent to one factory with another. This research aims to know and explain the influence of job satisfaction and organizational commitment against organizational citizenship behavior variables on employee sector corn starch and sweetener PT. Miwon Indonesia Gresik. This research is a type of causal research that uses a quantitative approach with a population of as many as 48 people and sampling techniques using non probability sampling with the samples as many as 48 employee sector corn starch and sweetener on PT. Miwon Indonesia Gresik. The result of this research shows that job satisfaction gives positive and significant influence to OCB. Organizational commitment has a positive and insignificant effect on OCB. Keywords: Job satisfaction, Organizational commitment, and OCB